Baricitinib for the treatment of rheumatoid arthritis and systemic lupus erythematosus: a 2019 update. (3rd July 2019) - Kubo, Satoshi; Nakayamada, Shingo; Tanaka, Yoshiya
ABSTRACT: Introduction : JAK, which constitutively binds to some cytokine receptors, plays an important role in cytokine signaling. While JAK is comprised of JAK1, JAK2, JAK3, and Tyk2, more than 40 types of cytokines transmit signals through JAK. Baricitinib is reported to be highly effective in the treatment of rheumatoid arthritis (RA) and is the second drug launched as a JAK inhibitor for RA. Area covered : We provide an overview of the mechanisms of action of baricitinib and its clinical implications in RA and other autoimmune diseases based on recent reports. This review outlines the mechanisms of action of baricitinib on human immune cells, the results of Phase III trials for RA, and the results of Phase II trials on SLE. Expert opinion : Baricitinib has potential to fine-tune various immune networks through a variety of mechanisms. Precision medicine is required in order to achieve maximum effects of targeted synthetic DMARDs including baricitinib and biological DMARDs in the future.